Mild Hyperthermia Accelerates Bone Repair by Dynamically Regulating iNOS/Arg1 Balance in the Early Stage - Jinhui Zhao; Yiping Luo; Lei Zhang; Yunfeng Chen; Yixing Chen; Xinhui Wu; Aihemaitijiang Aierken; Dilixiati Duolikun; Tianlong Wang; Zifei Zhou; Zhiqing Liu; Longpo Zheng (Advanced Science)
Abstract Mild hyperthermia therapy has garnered interest as an adjunctive treatment for bone repair. However, its optimal timing, duration, and underlying mechanisms remain unclear. In this study, how mild hyperthermia supports bone repair during the early stages is assesed. These findings reveal that mild hyperthermia accelerates bone regeneration by dynamically regulating inducible nitric oxide synthase/arginase 1 (iNOS/Arg1) balance. This process involves macrophage polarization to the M1 phenotype through iNOS activation, followed by a rapid transition to the M2 phenotype through Arg1 activation after 3 days of sustained mild hyperthermia. RNA‐Seq reveals that a single day of mild hyperthermia induced immune alterations aligned with the early inflammatory phase of bone repair, characterized by osteoclast activation, cell recruitment, and neovascularization, thereby preparing for the transition to the repair phase. Experiments involving subcutaneous abscesses, subcutaneous embedding, and critical cranial bone defects further confirm that early mild hyperthermia treatment dynamically regulates macrophage phenotypes. This regulation enhances early antibacterial activity, promotes angiogenesis, and facilitates the transition from inflammation to repair, ultimately accelerating bone‐defect repair. This study is the first to elucidate the dual temporal effects of early mild hyperthermia on immune regulation, offering insights into the optimal timing and duration of photothermal therapy following bone repair surgery.